Simulation Models for Estimating Optimal Vaccination Timing for Infectious Bursal Disease in Broiler Chickens in Paraguay - Suzuki, K.; Caballero, J.; Alvarez, F.; Faccioli, M.; Goreti, M.; Herrero, M.; Petruccelli, M. (International Journal of Poultry Science, 2009)
This study shows the results of estimating optimal vaccination timing for infectious bursal disease in broiler chickens in Paraguay, using spreadsheet simulation models. Fourteen flocks of broiler chicks were kept under observation. Sera were collected from randomly-selected 20 chicks per flock at 1, 4 and 8 days of age, and assayed by a commercial Enzyme-linked Immunosorbent Assay (ELISA) to evaluate Maternally Derived Antibody (MDA) titres. Deterministic (an age-based estimation method called the Deventer formula) and stochastic (through inclusion of uncertainty in the parameters) models were developed with the data. In the deterministic models, all the estimated optimal vaccination timings of each flock at the three sampling time points were between 16 and 24 days of age. In the stochastic models, each of the median optimal vaccination timings was estimated later than the corresponding point-estimate timing, generated by the deterministic version. Uniformity of the MDA titre distribution in the flocks was considered in relation to the number of vaccinations required. The ELISA results provide only a rough indication, in the case of deterministic model in particular. A stochastic version of the same model, in conjunction with the use of a concept of uniformity might give a solution to the problem.